Técnica Sanitária e o Traçado da Cidade: ê Representações de Planta e Plano no Trabalho do Urbanismo em Pernambuco na Década de 20 - Lira, José Tavares Correia de (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1995)
This article tries to examine issues that bind together plan of extension to mapping of a tow n as a sort of representation inaugurated from sanitary engineering concerns. It focuses on discussions taken place in Recife, Brazil, during the 1910s and 1920s, when the international debate on 'town planning' drew the attention of local engineers such as Moraes Rego, Saturnino de Brito, Paulo Guedes and José Estelita. Even though their former interestes being rested upon hygiene and landscape, they were gradually moving to recognize urbanistic problems as an autonomous field of analyses and intervention. From this new perspective, the town is to be considered analogous to the human body w ith its proper anatomy and patology, just as much as a combination of soil, subsoil, superficies and constructions